Novel Architecture Titanium Carbide (Ti3C2Tx) MXene Cocatalysts toward Photocatalytic Hydrogen Production: A Mini-Review - Van-Huy Nguyen (Nanomaterials, 2020)
Low dimensional transition metal carbide and nitride (MXenes) have been emerging as frontier materials for energy storage and conversion. Ti3C2Tx was the first MXenes that discovered and soon become the most widely investigated among the MXenes family. Interestingly, Ti3C2Tx exhibits ultrahigh catalytic activity towards the hydrogen evolution reaction. In addition, Ti3C2Tx is electronically conductive, and its optical bandgap is tunable in the visible region, making it become one of the most promising candidates for the photocatalytic hydrogen evolution reaction (HER). In this review, we provide comprehensive strategies for the utilization of Ti3C2Tx as a catalyst for improving solar-driven HER, including surface functional groups engineering, structural modification, and cocatalyst coupling. In addition, the reaming obstacle for using these materials in a practical system is evaluated. Finally, the direction for the future development of these materials featuring high photocatalytic activity toward HER is discussed.